The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1302/0301-620x.99b9.bjj-2016-1025.r2
|View full text |Cite
|
Sign up to set email alerts
|

The use of an anterior pelvic internal fixator to treat disruptions of the anterior pelvic ring

Abstract: The anterior pelvic internal fixator reduces the need for extensive open surgery and is a useful addition to the armamentarium for the treatment of anterior pelvic injuries. It is associated with injury to the LFCN in a third of patients. Cite this article: 2017;99-B.1232-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…ISS has become a commonly used technology in the treatment of pelvic posterior ring disruption. However, the ISS technique requires great surgical skill and continuous fluoroscopic guidance for appropriate screw insertion, and the risk of neurovascular injuries has been demonstrated to be higher than that for other techniques. A tension band plate placed in the posterior pelvic ring can provide sufficient stability for Tile C fractures.…”
Section: Introductionmentioning
confidence: 99%
“…ISS has become a commonly used technology in the treatment of pelvic posterior ring disruption. However, the ISS technique requires great surgical skill and continuous fluoroscopic guidance for appropriate screw insertion, and the risk of neurovascular injuries has been demonstrated to be higher than that for other techniques. A tension band plate placed in the posterior pelvic ring can provide sufficient stability for Tile C fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Most surgeons agree that external fixation is not the definitive treatment for pelvic anterior ring injuries, except in some special cases, and that internal fixation should be the priority. [ 1 , 3 , 6 , 12 , 14 , 18 ] Currently, there are 3 primary types of internal fixation used to treat pelvic anterior ring injuries, an internal fixator (INFIX), a reconstruction plate, and a cannulated screw. All 3 can be inserted with this minimally invasive technique.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the different types of anterior fixation showed that the likelihood of complications increases with the invasiveness of the stabilizing surgery. However, the categories given by the register do not allow to be very specific about biomechanical stability, which can be decisive 21,22 . Whether computer models based on finite element calculation methods will provide a reliable prediction method to calculate sufficiency of different stabilization techniques in individual patients, considering fracture morphology and bone quality, needs to be determined 23 .…”
Section: Discussionmentioning
confidence: 99%